Determination of petrophysical properties of Sadi Formation in Halfaya oil field, southern Iraq - Hashim, Mustafa M.; Farman, Ghanim M.; Askar, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This study aimed to evaluate the reservoir petrophysical properties (porosity, water saturation, and permeability) for optimal flow unit assessment within the Sadi Formation. Utilizing open hole logging data from five wells, the Sadi formation was divided into two rock units. The upper unit (A) is 45-50 meters thick, mainly consisting of limestone, mainly consisting of shaly limestone at the lower part. The lower unit (B) has a thickness of approximately 75-80 meters and is primarily composed of limestone, further subdivided into three subunits (B1, B2, B3). The average water resistivity is 0.04 ohm-m, and the average mud filtrate resistivity is 0.06 ohm-m. The Pickett plot was utilized to determine Archie parameters (tortuosity factor=1, cementation factor= 2, saturation exponent = 1.94). Petrophysical properties were determined through a sequence of operations involving lithology identification, shale volume estimation, porosity calculation, water saturation calculation, and permeability estimation. Lithology was identified using neutron, density and sonic logs with (N-D, M-N) cross plots, which show that the Sadi Formation is mainly limestone. The Gamma ray log was employed to estimate the shale volume of the Sadi Formation using the Larionov equation of old rock, resulting in a shale volume of 7%-58%. After calculating porosity using neutron-density logs, the resulting porosity matched the core porosity. Archie equation was used to calculate the formation’s water saturation, with water saturation less than 0.48 (cut-off) obtained in B1, B2 and B3 units. Finally, the formation permeability was estimated using the Flow Zone Indicator method, which provided a good match with core permeability. Porosity and water saturation were estimated with depth using Techlog software. The best hydrocarbon-holding unit is B2, which has the highest porosity, lowest water saturation, and the best permeability, with a thickness of 20.1 meters. As a result of this study, core plug analysis and well logging data identified eight distinct units in the Sadi Formation. There are three flow sub-units in upper Sadi (B1), three flow sub-units in Sadi (B2) and two sub-units in Sadi (B3). Additionally, it has been found that the marl rock unit (A2) separates the water-bearing zone (A1) from the oil-bearing zone (B).